2011
DOI: 10.1104/pp.111.176883
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Polyphosphate 5-Phosphatase7 Regulates the Production of Reactive Oxygen Species and Salt Tolerance in Arabidopsis      

Abstract: Plants possess remarkable ability to adapt to adverse environmental conditions. The adaptation process involves the removal of many molecules from organelles, especially membranes, and replacing them with new ones. The process is mediated by an intracellular vesicle-trafficking system regulated by phosphatidylinositol (PtdIns) kinases and phosphatases. Although PtdIns comprise a fraction of membrane lipids, they function as major regulators of stress signaling. We analyzed the role of PtdIns 5-phosphatases (5P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 83 publications
(119 reference statements)
6
77
0
1
Order By: Relevance
“…In recent years, PIs have emerged as central regulators of plant function and development, and a number of important and severe plant phenotypes have been reported when plant PI metabolism is perturbed Nelson, 2009, 2004;Chen et al, 2008;Ercetin et al, 2008;Golani et al, 2013;Gunesekera et al, 2007;Ischebeck et al, 2008Ischebeck et al, , 2011Ischebeck et al, , 2013Kaye et al, 2011;Kusano et al, 2008;Löfke et al, 2008;Mei et al, 2012;Novakova et al, 2014;Parker et al, 2000;Preuss et al, 2006;Rodriguez-Villalon et al, 2015;Sousa et al, 2008;Stenzel et al, 2008;Tejos et al, 2014;Wang et al, 2012;Williams et al, 2005;Zhong et al, , 2005. The perturbation of PI signaling components in Arabidopsis, for example, gives rise to a variety of phenotypes affecting multiple tissue types and aspects of plant development (summarized in Table 1).…”
Section: Pi Functions In Plantsmentioning
confidence: 99%
“…In recent years, PIs have emerged as central regulators of plant function and development, and a number of important and severe plant phenotypes have been reported when plant PI metabolism is perturbed Nelson, 2009, 2004;Chen et al, 2008;Ercetin et al, 2008;Golani et al, 2013;Gunesekera et al, 2007;Ischebeck et al, 2008Ischebeck et al, , 2011Ischebeck et al, , 2013Kaye et al, 2011;Kusano et al, 2008;Löfke et al, 2008;Mei et al, 2012;Novakova et al, 2014;Parker et al, 2000;Preuss et al, 2006;Rodriguez-Villalon et al, 2015;Sousa et al, 2008;Stenzel et al, 2008;Tejos et al, 2014;Wang et al, 2012;Williams et al, 2005;Zhong et al, , 2005. The perturbation of PI signaling components in Arabidopsis, for example, gives rise to a variety of phenotypes affecting multiple tissue types and aspects of plant development (summarized in Table 1).…”
Section: Pi Functions In Plantsmentioning
confidence: 99%
“…A number of studies have shown that NADPH oxidase-dependent ROS was induced by salt stress in Arabidopsis seedling roots and functioned as a positive regulator of salt tolerance by signaling salt stress responses. Mutations of genes involved in phosphatidylinositol signaling, which regulates vesicle trafficking, not only compromised salt tolerance but also the saltinduced intracellular production of ROS by NADPH oxidases (Kaye et al, 2011). Although NADPH oxidases normally reside in the plasma membrane, they can also be targeted by endocytosis and assembled into active forms in the internal membranes, and endosomal ROS production plays critical roles in a number of biological processes, including preinflammatory immune responses (Rubinek and Levy, 1993;Casbon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…When compared with wild-type plants, lip5 mutants accumulate increased levels of ubiquitinated protein aggregates, suggesting a possible role of LIP5-regulated MVB trafficking as a critical route for the degradation of heat-damaged proteins. Compromised salt tolerance of the lip5 mutants was associated with an increased accumulation of cellular NaCl but reduced levels of cellular reactive oxygen species (ROS), which have been implicated in the signaling of salt stress responses (Kaye et al, 2011;Xie et al, 2011). The roles of LIP5 and its phosphorylation by MPK3/6 in plant responses to heat and salt stresses were also investigated.…”
mentioning
confidence: 99%
“…геном арабидопсиса содержит 10 предста-вителей семейства генов мембраносвязанной субъединицы RBOH (Respiratory Burst Oxidase Homologs), обозначаемых как AtRboh (A, B, C, D, E, F, G, H, J, L) [37][38]. В геноме риса выявле-но девять генов, кодирующих каталитическую субъединицу NADPHоксидазы.…”
Section: Nadph-оксидаза растенийunclassified